Comparing engineering education systems among USA, EU, Philippines and South Africa - Alves, Anabela C. (Animo Repository, 2013)
Globalization has permeated our personal and professional lives and careers over the past two decades, to a point where communication, product development, and service delivery now are globally distributed. This means that the globalization of engineering practice is in effect. Large corporations tap into the global market for recruitment of engineers. However, the education of engineers occurs within the context of individual Higher Education Institutions. Engineers are educated with varying pacing and scoping of higher education programming with varying methods and pedagogy of higher education teaching. The expectations for engineering practice normed from the corporate side within the engineering marketplace, therefore, often do not match the widely dispersed educational experiences and outcomes of engineering education delivery. This gap brings challenges for all stakeholders, employers, higher education and the engineering graduate. But particularly, university education systems which traditionally are slow to respond to shifting market trends and demands, are expected to realign and restructure to answer this shortfall. A response to this shortfall has been prepared independently in different regions and countries. This paper discusses the response from Europe, USA, South Africa and Philippines. The European Commission started building a European Higher Education Area (EHEA) with the intention of promoting the mobility and the free movement of students and teachers in European tertiary education. US universities are introducing a design spine and strengthening students' systems thinking and problem solving competencies. Philippines is trying to be aligned with ABET system from US. South Africa universities are evolving to a solid core undergraduate engineering curriculum with a limited set of electives available to students which include project-based learning. This is intended to address the education-workplace gap as well. This theoretical paper will provide a comparison study of the differences between the Engineering Education in USA, EU, Philippines and South Africa. The authors will compare current trends and initiatives, aimed at improving the readiness and competitiveness of regional engineering graduates in the workplace. Given that several worthwhile initiatives are underway, it is possible that these initiatives will remain as disparate responses to the need for the globalization of engineering education. Lean performance management systems are widely used in engineering practice internationally and represent one possible rallying concept for the globalization of engineering education in order to address the education workplace gap. Therefore, this paper examines whether the introduction of a Lean Engineering Education philosophy is a worthwhile global curricular innovation for engineering courses. Copyright © 2013 by ASME.